2005
DOI: 10.1079/bjn20051481
|View full text |Cite
|
Sign up to set email alerts
|

Effect of site of starch digestion on portal nutrient net fluxes in steers

Abstract: Processing of maize grain is known to modulate the site of starch digestion, thus the nature and amount of nutrients delivered for absorption. We assessed the effect of site of starch digestion on nutrient net fluxes across portal-drained viscera (PDV). Three steers, fitted with permanent digestive cannulas and blood catheters, successively received two diets containing 35 % starch as dent maize grain. Diets differed according to maize presentation: dry and cracked (by-pass, BP) v. wet and ground (control, C).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 64 publications
(106 reference statements)
0
12
0
1
Order By: Relevance
“…The supplemental energy arising from postruminal starch digestion is beneficial to body adipose and protein retention (Reynolds 2006). The net portaldrained viscera release of ammonia was decreased with increasing duodenal starch flow (Noziere et al 2005). The concentration of blood urea N is highly correlated with the urinary N excretion rate (Kohn et al 2005).…”
Section: Doi: 1017221/8666-cjasmentioning
confidence: 81%
See 1 more Smart Citation
“…The supplemental energy arising from postruminal starch digestion is beneficial to body adipose and protein retention (Reynolds 2006). The net portaldrained viscera release of ammonia was decreased with increasing duodenal starch flow (Noziere et al 2005). The concentration of blood urea N is highly correlated with the urinary N excretion rate (Kohn et al 2005).…”
Section: Doi: 1017221/8666-cjasmentioning
confidence: 81%
“…Subacute ruminal acidosis and acute ruminal acidosis are severe metabolic diseases in high-producing ruminants, which originate from excessively low doi: 10.17221/8666-CJAS rumen pH due to the load of VFA. As a result, many attempts have been made to modify the nature and amount of starch available to rumen microbiota so as to shift part of starch digestion to the hindgut for the improvement of animal performance and feed efficiency as well as the absence of impairing animal health (Noziere et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…This is partly due to increased use of arterial glucose by PDV (Janes et al, 1985). However, with conventionally fed animals, this appears not associated with an increase in oxygen consumption by PDV (Reynolds et al, 1998;Noziè re et al, 2005), suggesting that other substrates are conserved (Huntington et al, 2006). Within the PDV, the mesentericdrained viscera (MDV) are the main users of arterial glucose, contributing to 70% of glucose uptake, as observed with non-starchy diet .…”
Section: Metabolism Of Vfa and Glucose By Portal-drained Visceramentioning
confidence: 99%
“…The results of present study and previous reports indicated that net PDV flux of ammonia-N might be affected by starch source and the processing of grain. Net PDV flux of ammonia-N was positively related to the ruminal ammonia-N concentration (Nozière et al, 2005). Therefore, the difference in net PDV flux of ammonia-N in goats between maize and wheat diets suggested there was difference in the ruminal ammonia-N concentration in goats fed maize and wheat diets.…”
Section: Discussionmentioning
confidence: 83%
“…In the present study, the net PDV ammonia-N flux of goats in wheat diet was higher than that of goats in maize diet. Nozière et al (2005) reported that portal net appearance of ammonia tended to decrease from 108 to 73 mmol/h when steers were fed the diets based on wet and ground maize, and the diets based on dry and cracked maize, respectively. The results of present study and previous reports indicated that net PDV flux of ammonia-N might be affected by starch source and the processing of grain.…”
Section: Discussionmentioning
confidence: 99%